Activation of the endogenous nociceptin system by selective nociceptin receptor agonist SCH 221510 produces antitransit and antinociceptive effect: a novel strategy for treatment of diarrhea‐predominant IBS. Issue 11 (15th July 2014) - Fichna, J.; Sobczak, M.; Mokrowiecka, A.; Cygankiewicz, A. I.; Zakrzewski, P. K.; Cenac, N.; Sałaga, M.; Timmermans, J.‐P.; Vergnolle, N.; Małecka‐Panas, E.; Krajewska, W. M.; Storr, M.
Abstract Background Diarrhea‐predominant irritable bowel syndrome (IBS‐D) is a functional gastrointestinal (GI) disorder, defined by the presence of loose stools and abdominal pain. In search for a novel anti‐IBS‐D therapy, here we investigated the nociceptin receptor (NOP)‐dependent effects in the GI tract. Methods A novel potent and selective NOP agonist SCH 221510 was used in the study. The effect of NOP activation on mouse intestinal motility was characterized in vitro and in vivo, in physiological conditions and in animal models of hypermotility and diarrhea. Well‐established mouse models of visceral pain were used to characterize the antinociceptive effect of the NOP activation. To provide additional evidence that the endogenous nociceptin system is a relevant target for IBS, NOP expression and nociceptin levels were quantified in serum and colonic biopsies from IBS‐D patients. Key Results SCH 221510 produced a potent NOP‐mediated inhibitory effect on mouse intestinal motility in vitro and in vivo in physiological conditions. The NOP agonist displayed an antidiarrheal and analgesic action after oral administration in animal models mimicking the symptoms of IBS‐D. Studies on human samples revealed a strong decrease in endogenous nociceptin system expression in IBS‐D patients compared with healthy controls. Conclusions & Inferences Collectively, mouse and human data suggest that the endogenous nociceptin system is involved in IBS‐D and may become a target for anti‐IBS‐D treatments using potent and selective synthetic NOP agonists.